지각된 관계적 지원이 한·중 대학생의 기업가적 동기에 미치는 영향: 자기효능감의 매개효과를 중심으로 - 양준환; Yang, Jun Hwan (벤처창업연구, 2015)
Strong ties such as family members, relatives and close friends have been widely acknowledged as a vital factor when a potential entrepreneur attempts to initiate entrepreneurial activity. Recent theoretical arguments focus that family social capital, a form of social capital, that is embedded in family relationships can contribute to venture creation as well as to the development of competitive advantage for established firms. Meantime, there have been arguments that the most dominant single entrepreneurial ethnic group in the world is the Chinese people, while the People's Republic of China is widely recognized as fast growing economic power that is driven by entrepreneurial ventures in a large scale. This study tests the effect of perceived relational supports typically being provided by family members, close relatives and friends on forming self-efficacy and entrepreneurial motivation of university students by using samples collected from 4 Korean Universities(Wonkwang, Baekseok, Soongsil and Dankook university) and Guangzhou University in China. The mediating of self-efficacy was also tested to gain better understanding of the role of the variable. The results of the study suggest that 1) both self-efficacy and entrepreneurial motivation are influenced positively by the perceived relational supports, 2) self-efficacy of university students affects their entrepreneurial motivation positively, 3) self-efficacy is appeared to be mediated partially for China in between perceived relational supports and entrepreneurial motivation, but the same variable is exhibited a full mediation in the same path of the research model for Korea, which was a distinction between the students of two countries in this study. Discussion and practical implication on the results are provided. 중국 사람은 세계에서 가장 기업가적인 단일민족으로 알려져 있으며 중국의 경제성장은 수많은 기업가들이 창업한 벤처기업들에 의해 견인되고 있다. 전 세계적으로 기업가정신과 청년창업활성화의 중요성이 강조되고 있는 시점에 본 연구는 미래의 잠재기업가들인 한국과 중국 대학생을 대상으로 대학생의 기업가적 특성을 살펴보기 위하여 진행하였다. 특히 본 연구는 청년창업활성화와 밀접한 관계가 있을 것으로 기대되는 가족, 친지들의 역할에 초점을 맞추어 분석해 보고자 한다. 이를 위해 선행연구결과들을 바탕으로 가족, 친척, 지인 등으로부터 제공되는 지각된 관계적 지원이 대학생들의 창업에 대한 자신감을 보여주는 자기효능감과 기업가적 동기에 영향을 주는가를 살펴보았다. 또한 대학생들의 창업에 대한 자기효능감이 관계적 지원에 의해 기업가적 동기에 매개효과를 갖는지 함께 살펴보았다. 본 연구의 표본은 원광대, 백석대, 숭실대 그리고 단국대 등 국내 네 곳 대학으로부터 268부, 중국은 광조우대학교로부터 259부를 확보하여 분석에 이용하였다. 분석 결과를 요약하면 다음과 같다. 지각된 관계적 지원은 한국과 중국 대학생들의 기업가적 동기에 모두 유의한 정의 영향을 미치는 것으로 나타났다. 지각된 관계적 지원은 양국 대학생들의 자기효능감에도 유의한 정의 영향을 미치고 있음을 확인하였다. 또한 자기효능감은 한국과 중국 대학생들의 기업가적 동기에 모두 유의한 영향을 미치는 것으로 나타났다. 끝으로 자기효능감은 한국의 경우 완전매개효과를 보인 반면 중국은 부분매개효과를 보이는 것으로 나타났다. 마지막으로 연구결과에 대한 논의 및 이론적, 실무적 시사점을 제시하였다.